(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background & objectives:Examination of the respiratory system by pulmonary function tests has been evolved as clinical tool in diagnosis,management and following up of respiratory diseases because it provides objective information about the state of an individual’s respiratory system. The present study aimed at evaluating pulmonary functionamong the smokers students of medical college of Babylon University and to comparetheir data with that of non-smokers students. Methods:A total of 80(45 smokers students and35 healthy young subjects) were randomlysampled for the study from the medical college of the Babylon University. The study population (20-25 year age group) had similar socioeconomicbackground. Each subject filled up the questionnaire to record their personaldemographic data, health status. Subjects with any history ofpulmonary diseases were excluded from the study. Results:The study showed significant differences between smoker and non-smoker groups regarding forced expiratory volume in one second (FEV1) and body mass index (BMI) (P ≤ 0.05), few of students had changes in respiratory function (mild obstruction), there was also significant relation between FEV1 and pack year, the students were not heavy smokers, no female student was found to be smoker. Conclusions: From the present study it can be concluded that the students in all groups have normal range of pulmonary function, most of the students smoke few number of cigarettes, and the smoking had considerable effect on lung function.